Structure–Activity Relationship of Plesiomonas shigelloides Lipid A to the Production of TNF-α, IL-1β, and IL-6 by Human and Murine Macrophages - Kaszowska, Marta; Wojcik, Marta; Siednienko, Jakub; Lugowski, Czeslaw; Lukasiewicz, Jolanta (Frontiers in Immunology, 2017)
Plesiomonas shigelloides is a Gram-negative bacterium that is associated with diarrheal disease in humans. Lipopolysaccharide (LPS) is the main surface antigen and virulence factor of this bacterium. The lipid A (LA) moiety of LPS is the main region recognized by target cells of immune system. Here, we evaluated the biological activities of P. shigelloides LA for their abilities to induce the productions of proinflammatory cytokines (TNF-α, IL-1β, and IL-6) by human and murine macrophages [THP-1 monocyte-derived macrophages and murine bone marrow-derived macrophages (BMDM)]. Four native P. shigelloides LA preparations differing in their phosphoethanolamine substitution, length, number, and saturation of fatty acids were compared with Escherichia coli O55 LA. The bisphosphorylated, hexaacylated and asymmetric forms of the P. shigelloides and E. coli LA molecules had similar activities in human and murine macrophages, indicating that shortening of the acyl chains in P. shigelloides LA had no effect on its in vitro activities. The PEtn decoration also had no impact on the interaction with the TLR4/MD-2 receptor complex. The heptaacylated form of P. shigelloides LA decorated with 16:0 exhibited strong effect on proinflammatory activity, significantly decreasing the levels of all tested cytokines in both murine and human macrophages. Our results revealed that despite the presence of shorter acyl chains and an unsaturated acyl residue (16:1), the bisphosphorylated, hexaacylated and asymmetric forms of P. shigelloides LA represent highly immunostimulatory structures.